DNA BARCODE CHARACTERIZATION OF MISTLETOE INFESTATION IN TEAK CLONAL SEED ORCHARD (CSO) IN PADANGAN, EAST JAVA PROVINCE, INDONESIA - Zainal Muttaqin; Sri Wilarso Budi; Basuki Wasis; Corryanti Corryanti; Iskandar Zulkarnaen Siregar (BIOTROPIA, 2017)
For effective teak plantation management, early detection system in controlling teak mistletoe requires various basic information, including degree of infestation and accuracy of the species names. Mistletoe infestations in teak and mistletoe species name have been reported, but there are still problems in identifying the correct species or subspecies due to morphological similarity. The objective of this study was to clarify the species identity of hemi-parasitic mistletoe plants, which were found in teak Clonal Seed Orchard (CSO) in Padangan, East Java Province, Indonesia using DNA barcodes. Species identification of teak mistletoe based on leaf morphological characteristics and universal DNA barcode regions (i.e. matK and rbcL) were carried out. The results showed that the Canonical Discriminant Analysis (CDA) could differentiate Dendrophthoe pentandra and Macrosolen tetragonus based on leaf morphological characteristics. Variables having high correlation to distinguish both species were length of petiole, width of the widest leaf, number of secondary leaf veins, leaf base shape, aspect ratio, form factor and perimeter ratio of diameter. The results of DNA barcoding showed that the two DNA barcode regions presented good amplification and sequence results. Both DNA barcode regions successfully differentiated two species i.e. D. pentandra and M. tetragonus which belong to Loranthaceae family and have similar leaf morphological characteristics. Those regions were also able to identify Viscum articulatum and other species belonging to Santalaceae family. These results suggested that the two DNA regions could become recommended universal DNA barcode for identifying teak mistletoe.